1994
DOI: 10.1002/neu.480250802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone on a sexually dimorphic frog muscle: Repeated in vivo observations and androgen receptor distribution

Abstract: In the present study the sexually dimorphic, androgen-sensitive flexor carpi radialis muscle (FCR) in male Xenopus laevis was viewed repeatedly in vivo to assess the influence of testosterone on muscle fiber size over a period of up to 12 weeks. Regions of the muscle innervated by different spinal nerves responded differently to testosterone treatment. Muscle fibers innervated by spinal nerve 2 (SN2) hypertrophied within 7 days in frogs that had been castrated and given testosterone-filled implants. This initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Similar androgendependent sex differences are found in the oblique muscles of the body wall (Tiagen et al, 1985;Girgenrath and Marsh, 2003), and in the flexor carpi radialis, the forelimb flexor muscle used by males to clasp females while they oviposit (Herrera and Regnier, 1991;Regnier and Herrera, 1993;Dorlöchter et al, 1994;Sidor and Blackburn, 1998).…”
Section: Steroid Hormones and Courtship Behavior In Male Amphibians: mentioning
confidence: 79%
“…Similar androgendependent sex differences are found in the oblique muscles of the body wall (Tiagen et al, 1985;Girgenrath and Marsh, 2003), and in the flexor carpi radialis, the forelimb flexor muscle used by males to clasp females while they oviposit (Herrera and Regnier, 1991;Regnier and Herrera, 1993;Dorlöchter et al, 1994;Sidor and Blackburn, 1998).…”
Section: Steroid Hormones and Courtship Behavior In Male Amphibians: mentioning
confidence: 79%
“…These differences appear to develop under the influence of hormonal regulation (Kelley, 1997;Kelley, 2004). A few studies have shown that the size dimorphism in forelimb muscles is also affected by testosterone (Dorlochter et al, 1994;Muller et al, 1969;Regnier and Herrera, 1993a;Regnier and Herrera, 1993b). But less is known about any differences in neuronal or muscle fiber cellular/molecular mechanisms in the limb muscles.…”
Section: Muscle Forcementioning
confidence: 99%
“…The effects of testosterone on the contractile properties of the flexor carpi radialis indicate that androgens play a role in adapting fibres in the muscle to the functional demands of clasping and further suggest that SN2 motor units and SN3 motor units are selectively important to the prolonged and brief patterns of flexion, respectively (Regnier & Herrera, 1993a). Indeed, the orientation of fibres innervated by SN2 with respect to the elbow joint (Dorlochter et al 1994) suggests that they are capable of producing greater rotational force (torque) and, therefore, are more important for the prolonged phase of clasping than those innervated by SN3 (Regnier & Herrera, 1993 b). The present results provide additional evidence for the differential roles of SN2 and SN3 motor units in clasping behaviour and suggest that testosterone enhances synaptic efficacy such that transmission is maintained in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated in vivo observations of shoulder region fibres in the flexor carpi radialis have indicated that changes in muscle fibre size induced by testosterone manipulation can occur over 1-2 weeks (Dorlochter et al 1994). To determine whether testosterone-associated changes in synaptic efficacy were occurring in less than 8 weeks, the percentage of subthreshold fibres innervated by SN2 was examined in muscles from frogs treated for 2 weeks (Fig.…”
Section: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation